Career Guidance and Introduction Services Career Students in SMKN 1 Enrekang - Handayani Sura; Mulyadi Mulyadi (Edumaspul: Jurnal Pendidikan, 2019)
The implementation objective of this research that was to find out how to service the guidance of a career and the introduction of career students in SMK 1 Enrekang. The method of this research that was qualitative with the subject of research that was the students in SMK 1 Enrekang. The results of research which based on the data results of the questionnaire service guidance career for choice of career showed that the importance of information about the type of work that was useful (40%) until (60%) strongly agrees. Consider interest (80%) strongly agree. Information world of work and the media type of the job (90%) highly agree. Jobs that require expertise (75%) strongly agree. The work of entertaining the crowd (60%) strongly agrees. Lacks of understanding the influence of education (60%) strongly agree, (35%) agree. Difficulty channelling hobbies (70%) strongly agree. Confused determine the school continued conformity ability (90%) highly agree While the data relationship introductions career against the choice of career showed the percentage of the will of the parents (50%) less agree. Work activities verbal such as lawyers (50%) did not agree. Work activities expression of self and creation (70%) did not agree. So it could be concluded that 60% of students who chosen the service guidance of a career that was implemented in the school had the benefit important for students and 80% of students who agree to be holding introductory career to give referrals.